RĂSPUNDEREA PENALĂ AJUDECĂTORULUI PENTRU INFRACȚIUNI CONTRA JUSTIȚIEI - Cozma, Daniela (SUPREMANCE OF LAW, 2018)
The article includes an overview of the crimes for which the magistrate is criminally responsible based on his status as a judge, according to the criminal law of Romania and the Republic of Moldova. Particular emphasis is placed on the juridical-criminal characteristic of the facts incriminated in art. 277, 280 and 283 of the New Criminal Code of Romania and art. 307, 308 par. (2) and art. 309 of the Criminal Code of the Republic of Moldova.
Keywords: magistrate; judge; criminal liability; criminal law; crime